Introduction to “Eve’s Curse: Redemptive Readings of Genesis 3:16” - Doukhan, Abi (Religions, 2025)
Genesis 3:16 has traditionally been interpreted as proof of woman’s inferiority, of her nefarious powers of seduction, and as a license for men to rule and master her [...]